The Role of Sufis in Connecting Aceh to the Global Islamic Network in the 17th Century - Affan, Muhammad (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2023)
In the 17th Century, the Sultanate of Aceh reached its peak. At that time, Aceh was connected to the Islamic world through diplomatic channels and maritime trade. In addition to these political and economic factors, Aceh's connectivity with the Islamic World was also connected through the Sufism network, where Sufis from Aceh sailed to Arabia and several other Muslim regions in order to study. These Sufis then returned to Aceh and established Islamic spiritual centers in Aceh and other Southeast Asian regions. The activities of these Sufis, in turn, helped connect Aceh to the global Islamic network. However, the actual role played by these Sufis in connecting Aceh to the global Islamic network has not been specifically explained because several studies that have been conducted tend to explain the pattern of the ulama network formed by Sufis in a broader scope. So that the more specific role of Sufis in connecting Aceh with the global Islamic network has not received adequate explanation. Based on these issues, this study aims to discuss the role of Sufis in building interconnectivity between Aceh and the global Islamic network in the 17th Century. The main question posed in this study is how the Sufis played their role as agents of connecting Aceh with the international Islamic network in the 17th Century. While, the method used in this study is the historical method where the source search is done through literature study. From the study, it is concluded that Sufis such as Hamzah Fansuri, Syamsuddin as Sumatrani and Shaykh Abdurrauf played an important role in connecting Aceh with the global Islamic network stretching from Southeast Asia to North Africa through wandering and sending students to study at international centers of Sufism in the Middle East. In addition, Sufis also established correspondence with other Sufis in other parts of the Islamic world. In this way, Aceh became connected to the global Islamic network. Keywords: Sufism, Islamic interconnectivity, Sultanate of Aceh, global Islamic network, Islamic history Pada Abad 17 Masehi, Kesultanan Aceh mencapai puncak kejayaannya. Pada masa itu, Aceh telah terhubung dengan Dunia Islam melalui jalur diplomatik dan perdagangan maritim rempah-rempah. Selain karena faktor politik dan ekonomi tersebut, konektivitas Aceh dengan Dunia Islam juga terhubung melalui jaringan sufisme, dimana para sufi dari Aceh berlayar ke Arab dan beberapa wilayah Muslim lainnya dalam kerangka menuntut ilmu. Para sufi ini kemudian kembali lagi ke Aceh dan mendirikan pusat-pusat spiritual Islam di Aceh dan kawasan Asia Tenggara lainnya. Aktivitas para sufi ini, pada gilirannya telah membantu menghubungkan Aceh dengan jaringan Islam global. Namun bagaimana peran sebenarnya yang dijalankan oleh para sufi ini dalam menghubungkan Aceh dengan jaringan Islam global belum dijelaskan secara khusus karena beberapa kajian yang telah dilakukan cenderung menjelaskan pola jaringan ulama yang terbentuk oleh para sufi dalam lingkup lebih luas. Sehingga peran sufi yang lebih spesifik dalam menghubungkan Aceh dengan jaringan Islam global belum mendapat penjelasan yang memadai. Berdasarkan pada persoalan tersebut, kajian ini bertujuan untuk mendiskusikan peran sufi dalam membangun interkonektivitas antara Aceh dengan jaringan Islam global pada Abad 17. Pertanyaan utama yang diajukan dalam kajian ini adalah bagaimana para sufi menjalankan peran sebagai agen penghubung Aceh dengan jaringan Islam internasional pada Abad 17. Metode yang dipergunakan dalam kajian ini adalah metode sejarah dimana penelusuran sumbernya dilakukan melalui studi kepustakaan. Dari kajian yang dilakukan diperoleh kesimpulan bahwa para sufi semacam Hamzah Fansuri, Syamsuddin as Sumatrani dan Syekh Abdurrauf telah berperan penting menghubungkan Aceh dengan jaringan Islam global yang membentang dari Asia Tenggara sampai ke Afrika Utara melalui pengembaraan dan pengiriman para murid-murid untuk belajar ke pusat-pusat sufisme internasional di kawasan Timur Tengah. Selain itu, para sufi juga menjalin hubungan korespondensi dengan sufi lainnya di belahan dunia Islam lainnya. Dengan cara tersebut, Aceh menjadi terhubung dengan jaringan Islam global. Kata kunci: sufi, interkonektivitas Islam, Kesultanan Aceh, jaringan Islam global, sejarah Islam ÙÙŠ Ø§Ù„Ù‚Ø±Ù† Ø§Ù„Ø³Ø§Ø¨Ø¹ Ø¹Ø´Ø± Ø§Ù„Ù…ÙŠÙ„Ø§Ø¯ÙŠ ØŒ ÙˆØµÙ„Øª Ø³Ù„Ø·Ù†Ø© Ø¢ØªØ´ÙŠÙ‡ Ø¥Ù„Ù‰ Ø°Ø±ÙˆØ© Ù…Ø¬Ø¯Ù‡Ø§ ØÙŠØ« Ø³ÙŠØ·Ø±Øª Ø¹Ù„Ù‰ ØªØ¬Ø§Ø±Ø© Ø§Ù„ÙÙ„ÙÙ„ Ø¹Ù„Ù‰ Ø§Ù„Ø³Ø§ØÙ„ Ø§Ù„ØºØ±Ø¨ÙŠ Ù„Ø³ÙˆÙ…Ø·Ø±Ø© ÙˆØµÙ„Øª Ø³Ù„Ø·Ù†Ø© Ø¢ØªØ´ÙŠÙ‡ Ø¥Ù„Ù‰ Ø°Ø±ÙˆØªÙ‡Ø§ ÙÙŠ Ø§Ù„Ù‚Ø±Ù† Ø§Ù„Ø³Ø§Ø¨Ø¹ Ø¹Ø´Ø±. ÙÙŠ Ø°Ù„Ùƒ Ø§Ù„ÙˆÙ‚Øª ØŒ ÙƒØ§Ù†Øª Ø£ØªØ´ÙŠÙ‡ Ù…Ø±ØªØ¨Ø·Ø© Ø¨Ø§Ù„Ø¹Ø§Ù„Ù… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ù‚Ù†ÙˆØ§Øª Ø§Ù„Ø¯Ø¨Ù„ÙˆÙ…Ø§Ø³ÙŠØ© ÙˆØ§Ù„ØªØ¬Ø§Ø±Ø© Ø§Ù„Ø¨ØØ±ÙŠØ©. Ø¨Ø§Ù„Ø¥Ø¶Ø§ÙØ© Ø¥Ù„Ù‰ Ù‡Ø°Ù‡ Ø§Ù„Ø¹ÙˆØ§Ù…Ù„ Ø§Ù„Ø³ÙŠØ§Ø³ÙŠØ© ÙˆØ§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠØ© ØŒ ÙƒØ§Ù† Ø§Ø±ØªØ¨Ø§Ø· Ø£ØªØ´ÙŠÙ‡ Ø¨Ø§Ù„Ø¹Ø§Ù„Ù… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ù…Ø±ØªØ¨Ø·Ù‹Ø§ Ø£ÙŠØ¶Ù‹Ø§ Ù…Ù† Ø®Ù„Ø§Ù„ Ø´Ø¨ÙƒØ© Ø§Ù„ØµÙˆÙÙŠØ© ØŒ ØÙŠØ« Ø£Ø¨ØØ± Ø§Ù„ØµÙˆÙÙŠÙˆÙ† Ù…Ù† Ø¢ØªØ´ÙŠÙ‡ Ø¥Ù„Ù‰ Ø´Ø¨Ù‡ Ø§Ù„Ø¬Ø²ÙŠØ±Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„Ø¹Ø¯ÙŠØ¯ Ù…Ù† Ø§Ù„Ù…Ù†Ø§Ø·Ù‚ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø£Ø®Ø±Ù‰ Ù„Ù„Ø¯Ø±Ø§Ø³Ø©. Ø¹Ø§Ø¯ Ù‡Ø¤Ù„Ø§Ø¡ Ø§Ù„ØµÙˆÙÙŠÙˆÙ† Ø¨Ø¹Ø¯ Ø°Ù„Ùƒ Ø¥Ù„Ù‰ Ø¢ØªØ´ÙŠÙ‡ ÙˆØ£Ù†Ø´Ø£ÙˆØ§ Ù…Ø±Ø§ÙƒØ² Ø±ÙˆØÙŠØ© Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙŠ Ø¢ØªØ´ÙŠÙ‡ ÙˆÙ…Ù†Ø§Ø·Ù‚ Ø£Ø®Ø±Ù‰ ÙÙŠ Ø¬Ù†ÙˆØ¨ Ø´Ø±Ù‚ Ø¢Ø³ÙŠØ§. Ø³Ø§Ø¹Ø¯Øª Ø£Ù†Ø´Ø·Ø© Ù‡Ø¤Ù„Ø§Ø¡ Ø§Ù„ØµÙˆÙÙŠÙŠÙ† Ø¨Ø¯ÙˆØ±Ù‡Ù… Ø¹Ù„Ù‰ Ø±Ø¨Ø· Ø£ØªØ´ÙŠÙ‡ Ø¨Ø§Ù„Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ©. ÙˆÙ…Ø¹ Ø°Ù„Ùƒ ØŒ ÙØ¥Ù† Ø§Ù„Ø¯ÙˆØ± Ø§Ù„ÙØ¹Ù„ÙŠ Ø§Ù„Ø°ÙŠ Ù„Ø¹Ø¨Ù‡ Ù‡Ø¤Ù„Ø§Ø¡ Ø§Ù„ØµÙˆÙÙŠÙˆÙ† ÙÙŠ Ø±Ø¨Ø· Ø¢ØªØ´ÙŠÙ‡ Ø¨Ø§Ù„Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ù„Ù… ÙŠØªÙ… Ø´Ø±ØÙ‡ Ø¹Ù„Ù‰ ÙˆØ¬Ù‡ Ø§Ù„ØªØØ¯ÙŠØ¯ Ù„Ø£Ù† Ø§Ù„Ø¹Ø¯ÙŠØ¯ Ù…Ù† Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„ØªÙŠ Ø£Ø¬Ø±ÙŠØª ØªÙ…ÙŠÙ„ Ø¥Ù„Ù‰ Ø´Ø±Ø Ù†Ù…Ø· Ø´Ø¨ÙƒØ© Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„ØªÙŠ Ø´ÙƒÙ„Ù‡Ø§ Ø§Ù„ØµÙˆÙÙŠÙˆÙ† Ø¹Ù„Ù‰ Ù†Ø·Ø§Ù‚ Ø£ÙˆØ³Ø¹. ØØªÙ‰ Ø£Ù† Ø§Ù„Ø¯ÙˆØ± Ø§Ù„Ø£ÙƒØ«Ø± ØªØØ¯ÙŠØ¯Ù‹Ø§ Ù„Ù„ØµÙˆÙÙŠÙŠÙ† ÙÙŠ Ø±Ø¨Ø· Ø£ØªØ´ÙŠÙ‡ Ø¨Ø§Ù„Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ù„Ù… ÙŠØªÙ„Ù‚ ØªÙØ³ÙŠØ±Ø§Ù‹ ÙƒØ§ÙÙŠØ§Ù‹. Ø¨Ù†Ø§Ø¡Ù‹ Ø¹Ù„Ù‰ Ù‡Ø°Ù‡ Ø§Ù„Ù‚Ø¶Ø§ÙŠØ§ ØŒ ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ù…Ù†Ø§Ù‚Ø´Ø© Ø¯ÙˆØ± Ø§Ù„ØµÙˆÙÙŠÙŠÙ† ÙÙŠ Ø¨Ù†Ø§Ø¡ Ø§Ù„ØªØ±Ø§Ø¨Ø· Ø¨ÙŠÙ† Ø£ØªØ´ÙŠÙ‡ ÙˆØ§Ù„Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© ÙÙŠ Ø§Ù„Ù‚Ø±Ù† Ø§Ù„Ø³Ø§Ø¨Ø¹ Ø¹Ø´Ø±. Ø§Ù„Ø³Ø¤Ø§Ù„ Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠ Ø§Ù„Ù…Ø·Ø±ÙˆØ ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‡Ùˆ ÙƒÙŠÙ Ù„Ø¹Ø¨ Ø§Ù„ØµÙˆÙÙŠÙˆÙ† Ø¯ÙˆØ±Ù‡Ù… ÙƒÙˆÙƒÙ„Ø§Ø¡ Ù„Ø±Ø¨Ø· Ø¢ØªØ´ÙŠÙ‡ Ø¨Ø§Ù„Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© ÙÙŠ Ø§Ù„Ù‚Ø±Ù† Ø§Ù„Ø³Ø§Ø¨Ø¹ Ø¹Ø´Ø±. Ø¨ÙŠÙ†Ù…Ø§ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‡ÙŠ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠØ© ØÙŠØ« ÙŠØªÙ… Ø§Ù„Ø¨ØØ« Ø¹Ù† Ø§Ù„Ù…ØµØ¯Ø± Ù…Ù† Ø®Ù„Ø§Ù„ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ø£Ø¯Ø¨. Ø®Ù„ØµØª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ø£Ù† Ø§Ù„ØµÙˆÙÙŠÙŠÙ† Ù…Ø«Ù„ ØÙ…Ø²Ø© ÙÙ†Ø³ÙˆØ±ÙŠ ÙˆØ³ÙŠÙ… Ø§Ù„Ø¯ÙŠÙ† Ù…Ø«Ù„ Ø³ÙˆÙ…Ø·Ø±Ø© ÙˆØ§Ù„Ø´ÙŠØ® Ø¹Ø¨Ø¯ Ø§Ù„Ø±Ø¤ÙˆÙ Ù„Ø¹Ø¨ÙˆØ§ Ø¯ÙˆØ±Ù‹Ø§ Ù…Ù‡Ù…Ù‹Ø§ ÙÙŠ Ø±Ø¨Ø· Ø¢ØªØ´ÙŠÙ‡ Ø¨Ø§Ù„Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ø§Ù„Ù…Ù…ØªØ¯Ø© Ù…Ù† Ø¬Ù†ÙˆØ¨ Ø´Ø±Ù‚ Ø¢Ø³ÙŠØ§ Ø¥Ù„Ù‰ Ø´Ù…Ø§Ù„ Ø¥ÙØ±ÙŠÙ‚ÙŠØ§ Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„ØªØ¬ÙˆÙ„ ÙˆØ¥Ø±Ø³Ø§Ù„ Ø§Ù„Ø·Ù„Ø§Ø¨ Ù„Ù„Ø¯Ø±Ø§Ø³Ø© ÙÙŠ Ø§Ù„Ù…Ø±Ø§ÙƒØ² Ø§Ù„Ø¯ÙˆÙ„ÙŠØ©. Ø§Ù„ØªØµÙˆÙ ÙÙŠ Ø§Ù„Ø´Ø±Ù‚ Ø§Ù„Ø£ÙˆØ³Ø·. Ø¨Ø§Ù„Ø¥Ø¶Ø§ÙØ© Ø¥Ù„Ù‰ Ø°Ù„Ùƒ ØŒ Ø£Ù†Ø´Ø£ Ø§Ù„ØµÙˆÙÙŠÙˆÙ† Ø£ÙŠØ¶Ù‹Ø§ Ù…Ø±Ø§Ø³Ù„Ø§Øª Ù…Ø¹ ØµÙˆÙÙŠÙŠÙ† Ø¢Ø®Ø±ÙŠÙ† ÙÙŠ Ø£Ø¬Ø²Ø§Ø¡ Ø£Ø®Ø±Ù‰ Ù…Ù† Ø§Ù„Ø¹Ø§Ù„Ù… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ. ÙˆØ¨Ù‡Ø°Ù‡ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© ØŒ Ø£ØµØ¨ØØª Ø£ØªØ´ÙŠÙ‡ Ù…ØªØµÙ„Ø© Ø¨Ø§Ù„Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ©. Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙØªØ§ØÙŠØ©: Ø§Ù„ØµÙˆÙÙŠØ© ØŒ Ø§Ù„ØªØ±Ø§Ø¨Ø· Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ ØŒ Ø³Ù„Ø·Ù†Ø© Ø¢ØªØ´ÙŠÙ‡ ØŒ Ø§Ù„Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© ØŒ Ø§Ù„ØªØ§Ø±ÙŠØ®